2017
DOI: 10.1093/annweh/wxx040
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Respirable Dust and Crystalline Silica Controls During Simulated Performance of Stone Countertop Fabrication Tasks With Powered Hand Tools

Abstract: Objectives Workers who fabricate stone countertops using hand tools are at risk of silicosis from overexposure to respirable crystalline silica. This study explored the efficacy of simple engineering controls that can be used for dust suppression during use of hand tools by stone countertop fabricators. Methods Controlled experiments were conducted to measure whether wet methods and on-tool local exhaust ventilation (LEV) reduced respirable dust exposures during use of various powered hand tools on quartz-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Most of the studies reviewed reported that basic preventive measures for controlling occupational exposure and for protecting the health of workers were not adopted, or not properly adopted. In fact, no effective measures, such as general or mounted-tool local exhaust ventilation systems or wet-cut methods, were implemented to suppress dust generation/exposure when working on AS [20,50,51]. In addition, machinery and tools were not properly set up and they did not undergo the prescribed routine checks [43].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reviewed reported that basic preventive measures for controlling occupational exposure and for protecting the health of workers were not adopted, or not properly adopted. In fact, no effective measures, such as general or mounted-tool local exhaust ventilation systems or wet-cut methods, were implemented to suppress dust generation/exposure when working on AS [20,50,51]. In addition, machinery and tools were not properly set up and they did not undergo the prescribed routine checks [43].…”
Section: Discussionmentioning
confidence: 99%
“…It is our recommendation that manipulation processes involving the use of power tools for cutting, grinding, and polishing artificial stone countertops containing high concentrations of crystalline silica (i.e., above those of natural stones) include dust suppression both on the tools and on the work-stations. Aggressive engineering controls, such as the use of dust hoods/shrouds on the grinders, down-draft tables, and water jet sprays [50], should be designed and implemented for each specific operation to keep dust levels at a minimum, not only to avoid exposure during the manipulation process, but also to avoid dust resuspension when handling the materials and moving around the work environment. A floor drainage system should be used to clean the floors before the wet dust dries.…”
Section: Discussionmentioning
confidence: 99%
“…Silicosis among stonemasons in the AS benchtop fabrication and installation industry has been reported ( Qi and Echt, 2016 ; Johnson et al , 2017 ) with increasing frequency since 2011 ( Leso et al , 2019 ). Affected workers have been frequently reported to be young and still actively employed ( Hoy et al , 2018 ; Leso et al , 2019 ; MartĂ­nez GonzĂĄlez et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%